2017
DOI: 10.1158/1535-7163.mct-17-0405
|View full text |Cite
|
Sign up to set email alerts
|

The DNA Repair Inhibitor Dbait Is Specific for Malignant Hematologic Cells in Blood

Abstract: Hematologic malignancies are rare cancers that develop refractory disease upon patient relapse, resulting in decreased life expectancy and quality of life. DNA repair inhibitors are a promising strategy to treat cancer but are limited by their hematologic toxicity in combination with conventional chemotherapies. Dbait are large molecules targeting the signaling of DNA damage and inhibiting all the double-strand DNA break pathways. Dbait have been shown to sensitize resistant solid tumors to radiotherapy and pl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…In addition, synergy between AsiDNA and conventional cancer therapies (etoposide, cyclophosphamide and radiotherapy) has been shown in 8 out of 10 lines of lymphoma and leukemia cell line. Moreover, AsiDNA increases DNA-damaging agent sensitivity of tumor cells without affecting normal hematological white blood cells [42]. These results are promising and AsiDNA is currently tested on phase I clinical trial as a monotherapy in advanced solid tumor.…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 97%
“…In addition, synergy between AsiDNA and conventional cancer therapies (etoposide, cyclophosphamide and radiotherapy) has been shown in 8 out of 10 lines of lymphoma and leukemia cell line. Moreover, AsiDNA increases DNA-damaging agent sensitivity of tumor cells without affecting normal hematological white blood cells [42]. These results are promising and AsiDNA is currently tested on phase I clinical trial as a monotherapy in advanced solid tumor.…”
Section: Targeting Dna-pk With Inhibiting Moleculesmentioning
confidence: 97%
“…Moreover, H2AX phosphorylation by DNA-PK was exclusive to tumour cells, thus indicating sparing of surrounding non-tumourigenic tissue [ 131 ]. A signal-interfering DNA (AsiDNA), which is a cholesterol-conjugated member of the Dbait family, induces preferential toxicity towards tumourigenic tissue whilst sparing non-tumourigenic hematologic cells and preserving immune function [ 132 ]. Thierry et al (2017) reported the induction of necrotic and apoptotic cell death by AsiDNA through p53-independent mechanisms in several lymphoma and leukaemia cell lines [ 132 ].…”
Section: Deoxyribonucleic Acid Repair Pathways As Therapeutic Tarmentioning
confidence: 99%
“…A signal-interfering DNA (AsiDNA), which is a cholesterol-conjugated member of the Dbait family, induces preferential toxicity towards tumourigenic tissue whilst sparing non-tumourigenic hematologic cells and preserving immune function [ 132 ]. Thierry et al (2017) reported the induction of necrotic and apoptotic cell death by AsiDNA through p53-independent mechanisms in several lymphoma and leukaemia cell lines [ 132 ]. AsiDNA enters cells through low density lipoprotein (LDL) receptors and subsequently activates DNA-PK [ 132 ].…”
Section: Deoxyribonucleic Acid Repair Pathways As Therapeutic Tarmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematological malignancies (HM) account for approximately 10% of all newly diagnosed cancers and are usually characterized by genetic defect in the form of chromosomal translocation or breakpoint/fusion [ 4 ]. Many HM run a chronic relapsing course, culminating in therapy resistance with multiple lines of therapy [ 5 ]. Development of resistance to DNA-damaging chemotherapy agents such as cisplatin, cyclophosphamide, chlorambucil, and temozolomide can be somewhat mitigated with concurrent inhibition of DNA repair pathways, increasing cytotoxicity [ 6 ] and hence therapeutic efficacy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%